Perkembangan Pendidikan Islam di Era Khulafa Ar-Rasyidin - Mardinal Tarigan; Husna Khairuzzakiah; Vira Annisa Barus (Jurnal Dirosah Islamiyah, 2024)
This research discusses the history of Islamic education before and during the era of the Rashidun Caliphate, focusing on the earlier period led by Prophet Muhammad and the period of the Rashidun Caliphs, which includes the leadership of Abu Bakr, Umar ibn Khattab, Uthman ibn Affan, and Ali ibn Abi Talib. The study employs a Literature Review approach to gather and analyze data from various relevant sources. The findings indicate that Islamic education during these periods experienced significant development, with each caliph making unique contributions to the formation and dissemination of Islamic education. However, there were also challenges and disruptions affecting the educational process, especially during the caliphate of Ali ibn Abi Talib. This research provides profound insights into the role of Islamic education in shaping the identity and character of Muslim communities and contributes to a better understanding of the development of Islamic education in the present and future.